Alyne e seus espectros: breve estudo sobre violência obstétrica no Brasil - Vasconcelos, Desirée Cristina Rodrigues (2018)
In 2010, a survey of the Perseu Abramo Foundation, reported that 1/4 of Brazilian women suffer from Obstetric Violence (VO). Improving maternal health was one of the millennium goals of the meeting of the 191 member states of the United Nations in the year 2000. Despite the decrease in maternal mortality (MM) worldwide, Brazil was not able to reduce it to the satisfaction and continues with indicators considered high by WHO (62 maternal deaths per 100,000 live births). In this study, VO and MM were studied, starting from Alyne Pimentel, a black and poor girl from the city of Belfort Roxo, in Rio de Janeiro, who died in 2002 due to attendance health professionals. The study expanded from the reports of women who had suffered a violation of their Reproductive and Sexual Rights, whose stories were widely publicized, either by the media or by the NGO ARTEMIS database. The study proposed here confirmed that VO and MM continue to occur in profusion in Brazil, in situations similar to that of Alyne Pimentel, and the humanization of care, observance of practices based on scientific evidence, and delivery houses remain ideal. achieved and not a reality. Finally, it was intended to understand the reasons why, up to the present moment, only a small fraction of reports of abuses have reached the Judiciary, specifically the higher courts - STF and STJ. It was concluded that there is a serious lack of access to justice and that even in Brazil, there is no specific criminological type for VO, there are legal instruments to hold criminals accountable, both in civil and criminal cases, and under criminal law.